Immunomodulatory role of vitamin D and emerging immunotherapies in hepatocellular carcinoma - Chiriva-Internati, Maurizio; Grizzi, Fabio; Monari, Marta Noemi; Taverna, Gianluigi; Figueroa, Jose A.; Daoyan, Wei; Bresalier, Robert S. (Frontiers in Nutrition, 2025)
Hepatocellular carcinoma (HCC) is one of the most common cancers globally, with nearly 1 million new cases diagnosed annually. It is a complex disease, with hepatitis B virus (HBV) and hepatitis C virus (HCV) infections being the most common etiological factors worldwide. Despite advances in therapy, survival rates for advanced and/or metastatic HCC remain low, with mortality rates 2.3 times higher in men than women. The liver’s immune system typically maintains an anti-inflammatory environment, contributing to immune tolerance to exogenous, food-derived antigens. However, disruption of the balanced interplay between immune factors within the hepatic microenvironment—due to viral hepatitis, excessive alcohol intake, non-alcoholic fatty liver disease (NAFLD) or non-alcoholic steatohepatitis (NASH)—can lead to chronic inflammation, oxidative stress, a cumulative mutational burden, cirrhosis, and eventually, malignant transformation. Once HCC is established, however, a functional pro-inflammatory immune response becomes critical to controlling tumor progression, as evidenced by the recent success of immune checkpoint inhibitor (ICI) treatments in HCC patients. In addition to ICIs, other novel immunotherapeutic intervention strategies, such as cancer vaccines and adoptive T cell therapies, are currently being investigated. Furthermore, adequate nutrition plays a critical role in modulating immune function, with vitamin D being a key nutrient for immune/regulation. In this review, we will discuss the potential role of vitamin D in HCC immunity and recent immunotherapeutic advances in the management of this malignancy.